NAASR Notes. (9th June 2015) - Sheedy, Matt
Abstract : NAASR Notes began as feature with the Bulletin for the Study of Religion blog, where we invite members of the North American Association for the Study of Religion to describe books they are reading and/or research and writing projects that will be of interests to scholars in the field. The following are the first five pieces in the series: by Sean Durbin, Jason Blum, Russell McCutcheon, Naomi Goldenberg, and Dennis LoRusso.